التكامل بين تقنيتي المحاسبة المرنة و تكلفة على اساس المواصفات بهدف تخفيض التكاليف (دراسة تطبيقية في معمل حلبجة للخرسانة الجاهزة) - نجم, بصيرة مجيد; فرج, سەروەر مجید (Sulaimani Journal for Humanities, 2022)
This research aims to study the steps of applying cost technology based on specifications to measure costs of products and to identify lean accounting in terms of concept, principles, objectives and requirements and to indicate the possibility of achieving integration between the two cost techniques based on specifications and lean accounting in order to reduce costs. The results of the research show that the cost technique can be applied on the basis of specifications through the application of one of the lean accounting tools, which is the performance measurement link scheme, and one of the most important measures of this tool is the method of characteristics and advantages. The research shows that the production cost was calculated according to the value stream. It was found that the production cost under the value stream is equal to the production cost under the specification-based cost technique. This means that it is possible to apply a cost based on the specifications instead of applying the value stream, as the steps of applying the cost are based on the specifications. Clearer and easier to apply current value. The research also shows that it is possible to achieve integration between the two cost techniques on the basis of specifications and lean accounting in order to reduce costs.